تثمين التارث الثقافي المادي في المناطق الخاصة - حاج إسماعيل محمد الأمين (جامعة البليدة2؛ كلية الحقوق والعلوم السياسية, 2025)
يتناول موضووووووووووووي بحلنا تلمين التارل اللقافي المادق في المنا ال ا وووووووووووة، الذق يدخل في إ ار الاهتمام بالتارل اللقافي المادق، كونه مهم لهوية الأمة وتاري يها، ودليل اسووووووووووووووتمارريتها ع ر العصووووووووووور، بحيث عزز هذا الاهتمام حماية التارل اللقافي المادق من جهة وكذا العمل على تلمينه في المنا ال ا ة من جهة ثانية. بحيث تعد الدارسوووووووووووة متطلبا للواقع الذق يل ت ويشوووووووووووير الى الإهمال والتدهور التي تعاني من ة ، كون ان الاليات القانونية التي وضوووووووووعت من اجل حمايته أ وووووووووبحت قا ووووووووور ، المنا ال ا وووووووووة ال ضوووووووووو ي ة مقارنة بما يتطلب اتيجيات المتبعة في عملية التلمين لا تز بالإضووووووووووافة كون ان الاسووووووووووتر التارل المادق. ومنه برزت الإشوووووكالية، المتمللة في كيجية تجلووووويد الحماية الملوووووتدامة للتارل اللقافي المادق، بالإضووووافة الى افام تلمينه في المنا ال ا ووووة وب اعلية، لكي يحق اسووووتدامته واسووووتمارريته ليلعب الدور المنوط به من أجل التنمية المحلية. لقد قمنا من خلال هذا البحث بالاعتماد على التحليل والو وووم، من خلال تحليل النصوووو القانونية التي أوردها المشووووووووووووووري الجازئ ر ق والتي لها علاقة بالحماية القانونية للتارل اللقافي المادق، بالإضافة لم تلم ال ارمج الو نية ذات الصلة بالموضوي، مع الوقوف على حالة المنا ال ا ة وواقعها المحلي. وأهم موا خلص اليوه البحوث ان الحموايوة القوانونيوة التي ك لهوا القوانون لم تعود ، من نتوائج مهموة كافية بلوووووووووو ب قلة التنلووووووووووي والعمل وف ا ر تشوووووووووواركية بين م تلم ال اعلين، بالإضووووووووووافة الى قلة ادة موجودة لكن بالإضووووووووافة الى كون الإر ها ، ونقص الوعي المجتمعي ، الإمكانيات ال ا ووووووووة بالتلمين غير كافية، لكي يصبح التارل المادق كأحد ال دائل الغير تقليدية للاقتصاد الو ني. ان تط ي مجموعة المعطيات التي أو ووووووى بحلنا بالهيام بها على غارر ضوووووورورة العمل على إيجاد اليات قانونية وت عيلها، دمج المجتمع المحلي في عملية التلمين، مع العمل أيضوا على انتهاج ‌ اسوووووووووووووتارتيجيات فعالة تجعل للتارل اللقافي المادق دوار مهما من خلال ال ارمج التنموية واللوووووووووووووياحية الملتدامة. الكلمات المفتاحية: المنا ال ا ة، التارل المادق، التلمين. The subject of our research deals with the valorization of tangible cultural heritage in special areas, a topic that falls within the framework of interest in tangible cultural heritage, as it is important for the nation’s identity and history, and evidence of its continuity throughout the ages, so that this interest has strengthened the protection of tangible cultural heritage on the one hand, as well as working to value it in special areas on the other hand.second. So, the study is a requirement of reality that proves and indicates the neglect and deterioration that private areas suffer from, since the legal mechanisms that were put in place to protect them have become deficient, in addition to the fact that the strategies used in the valuation process are still weak compared to what the tangible heritage requires. From it, the problem emerged, which is how to effectively embody the sustainable protection of tangible cultural heritage, in addition to the prospects for valuing it in special areas, in order to achieve its sustainability and continuity to play the role assigned to it for local development. Through this research, we have relied on analysis and description, by analyzing the legal texts mentioned by the Algerian legislator that are related to the legal protection of tangible cultural heritage, in addition to various national programs related to the subject, while examining the situation of special areas and their local reality. The most important findings of the research are that the legal protection guaranteed by the law is no longer sufficient due to the lack of coordination and work according to participatory frameworks between various actors, in addition to the lack of capabilities for valuation, and the lack of community awareness, in addition to the fact that the will exists, but it is not sufficient, for it to become The tangible heritage is one of the unconventional alternatives to the national economy. Applying the set of data that our research recommended doing is similar to the necessity of working to find and activate legal mechanisms, integrating the local community into the valuation process, while also working to adopt effective strategies that give tangible cultural heritage an important role through sustainable development and tourism programs. Keywords: Special areas, tangible heritage, valorization
Keywords: المناطق الخاصة; الثراث المادي